Analisis Tema pada Novel Dua Belas Cerita Glenn Anggara Berdasarkan Tingkatan Tema Menurut Shipley - Bela, Sofi Esa (Fakultas Ilmu Budaya Universitas Diponegoro, 2023)
This research is motivated by the author who wants to determine the theme in the story excerpts of Glen Anggara's novel Dua Belas Cerita based on Shipley's categories, as evidenced by the data according to the story fragments on each page. The purpose of this research is to analyze the themes in Glen Anggara's novel Dua Belas Cerita based on Shipley's categories. The benefits of this research are to add insight and knowledge about the categories of theme levels according to Shipley in Glen Anggara's novel Dua Belas Cerita which refers to daily activities. The research theory is the level of themes according to Shipley, namely physical themes, organic themes, selfish themes, divine themes, and social themes. The type of research used is descriptive qualitative. The data used, namely analyzing the plot on each fragment of the story per page. The author examines the plot of the novel using data analysis techniques. The author collects accurate data using documentation techniques. In this study, the source of document data is the novel Twelve Stories of Glen Anggara by Luluk HF. The results showed that the level of theme according to Shipley was a social theme with a total of 133 data from 27 chapters in the story excerpt.